HUBUNGAN JENIS KELAMIN, AKTIFITAS FISIK DAN STATUS GIZI DENGAN KESEGARAN JASMANI ANAK SEKOLAH DASAR - Yoga H, Anindya; Purnamasari, Dyah Umiyarni; Kusnandar, Kusnandar (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2014)
ABSTRACT   The physical freshness have to be applied among the children between 6 - 12 years old. At that years, the children can do all the activities optimally and confidently. Hence, the influence factors included are : gender/sex, nutrition and physical activities. Analytical study used by the research by cross sectional method. Gathering the samples done by purposive sample technique. The samples are from 33 students, which is the students from grade VI state elementary 1 Rempoah, Baturaden District. Analytical data include of chi-square test to analyze the relation between gender/sex, nutrition status and physical activities with the physical freshness to children (p<0,05). The result of the study showed that there is the correlation between physical activities (p= 0,014) to the children and there is not correlation between gender/sex (p= 0,550), nutrition status (p= 0,649) and physical freshness to the children. Hopefully, the next researcher can do the research not only by the factors of gender or sex, physical activities and nutrition status but also, from the other factors can be influence.   Keyword : gender, nutrition status, physical activity, physical freshness, elementary school student.  Kesmasindo, Volume 7( 1) Juli 2014, Hal 31-38